Religion-regime relations in Zimbabwe
1 online resource.
Keywords: This book explores religion-regime relations in contemporary Zimbabwe to identify patterns of co-operation and resistance across diverse religious institutions. Using co-operation and resistance as an analytical framework, the book shows how different religious organisations have interacted with Emmerson Mnangagwa's "Second Republic", following Robert Mugabe's departure from the political scene. In particular, through case studies on the Zimbabwe Council of Churches, Zimbabwe Catholic Bishops Conference and Pentecostals, African Traditional Religions, Islam, and others, the book explores how different religious institutions have responded to Mnangagwa's new regime. Chapters highlight the complexities characterising the religion-regime interface, showing how the same religious organisation might co-operate and resist at the same time. Furthermore, the book compares how religious institutions co-operated or resisted Mugabe's earlier regime to identify patterns of continuity and change. Overall, the book highlights the challenges of deploying simplistic frames in efforts to understand the interface between politics and religion. A significant contribution to global scholarship on religion-regime interfaces, this book will appeal to academics and students in the field of Religious Studies, Political Science, History and African Studies